Reputation, social identity and social conflict - John Smith (Rutgers University, Department of Economics, 2007)
We interpret the psychology literature on social identity and examine its implications in a population partially composed of such agents. We model a population of agents from two exogenous and well defined social groups. Agents are randomly matched to play a reduced form bargaining game. We show that this struggle for resources drives a conflict through the rational destruction of surplus. We assume that the population contains both rational players and behavioral players. Behavioral players aggressively discriminate against members of the other social group. The existence and specification of the behavioral player is motivated by the social identity literature. For rational players, group membership has no payoff relevant consequences. We show that rational players can contribute to the conflict by aggressively discriminating and that this behavior is consistent with existing empirical evidence. Our paper relates to the empirical literature which finds that our measure of social heterogeneity tends to be increasing in economic variables which we interpret as signifying inefficiency. We provide an explanation that, as social groups compete for the benefits of public goods, disagreement and inefficiency can result. Our work also relates to the social conflict literature, which examines the relationship between macro level factors such as unemployment and civil disturbances. This literature finds that the amount of social conflict tends to be increasing in what we refer to as the inequitability of the environment.
Keywords: C72; D74; L14; 330; Reputation; conflict; identity; Soziale Beziehungen; Sozialer Konflikt; Sozialpsychologie; Prestige; Verhandlungstheorie; Theorie